Securing Electronic Medical Records Using Modified Blowfish Algorithm - Theda Flare Ginoy Quilala; Ariel M Sison; Ruji P Medina (IAES Indonesian Section, 2018)
EMR helped improve services to patients by delivering organization and accuracy of patient information, but issues regarding security breaches and medical identity theft are growing concerns. This paper enhance the current EMR system by integrating modified encryption. The simulation used modified Blowfish algorithm in an EMR system that focuses on four goals: 1) define the requirements, 2) design and identify features, 3) develop the EMR incorporating added security mechanism using modified Blowfish algorithm, and 4) test the application with sample data. Based on the results, the incorporation of the encryption was successful based on testing and checking done on the input terminal and the database server. Data inputted on the EMR system was successfully encrypted before transmission and decrypted only on the terminal for viewing. Performance results show that without encryption, saving took an average of 87.8ms while encrypted, it acquired 88.8ms, a difference of 1ms can be noted. The minimal difference is because of the size of the data. The average decryption time of all records using modified algorithm took 1342ms while using plaintext took 1322ms. The decryption time is higher by 20ms due to the application of the decryption algorithm.